2001
DOI: 10.2460/javma.2001.218.245
|View full text |Cite
|
Sign up to set email alerts
|

Use of medetomidine and ketamine for immobilization of free-ranging giraffes

Abstract: Medetomidine and KET was an effective immobilizing combination for free-ranging giraffes; however, at the dosages used, it does not induce adequate analgesia for major manipulative procedures. Quality of induction and immobilization were enhanced if the giraffe was calm. Reversal was rapid and complete following injection of ATP.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
18
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(25 citation statements)
references
References 5 publications
4
18
1
Order By: Relevance
“…We interpret these results to indicate addition of hyaluronidase to XZT at 150 IU per dart was generally effective to reduce the amount of drug needed and hasten induction for capture of free-ranging polar bears. We point out, however, the amount we added per dart in this study was considerably less than amounts reported by other sources, which vary from 2,000 IU for African elephants (Osofsky, 1997) to 7,500 IU for giraffes (Bush et al, 2001), but similar to amounts cited in earlier reports (for example, Haigh, 1979;Trillmich, 1983;Clausen et al, 1984). At the time we conducted this study, we were constrained to using a small amount by lack of availability of hyaluronidase in Canada, limiting us to its importation under government approval as Amphadase, and by the need to keep dart volumes to a minimum.…”
contrasting
confidence: 71%
See 1 more Smart Citation
“…We interpret these results to indicate addition of hyaluronidase to XZT at 150 IU per dart was generally effective to reduce the amount of drug needed and hasten induction for capture of free-ranging polar bears. We point out, however, the amount we added per dart in this study was considerably less than amounts reported by other sources, which vary from 2,000 IU for African elephants (Osofsky, 1997) to 7,500 IU for giraffes (Bush et al, 2001), but similar to amounts cited in earlier reports (for example, Haigh, 1979;Trillmich, 1983;Clausen et al, 1984). At the time we conducted this study, we were constrained to using a small amount by lack of availability of hyaluronidase in Canada, limiting us to its importation under government approval as Amphadase, and by the need to keep dart volumes to a minimum.…”
contrasting
confidence: 71%
“…Use of hyaluronidase as a component of immobilizing drug mixtures has been promoted to accelerate drug absorption from muscle or fat and reduce induction times for several species of terrestrial mammals, including white-tailed deer (Odocoileus virginianus; Allen, 1970), moose (Alces alces; Haigh, 1979), muskoxen (Ovibos moschatus; Clausen et al, 1984), black rhinoceroses (Diceros bicornis; Kock, 1992), African elephants (Loxodonta africana; Kock et al, 1993), and giraffes (Giraffa camilopardalis; Bush et al, 2001), as well as several species of marine mammals (Pinnipeds; Gales, 1989). Hyaluronidase is a naturally occurring enzyme generally extracted from bovine or ovine testes and used widely in human medicine (Girish and Kemparaju, 2007) as a diffusing substance to increase permeability of connective tissue through hydrolysis of hyaluronic acid, a polysaccharide found in the intracellular ground substance of connective tissue.…”
mentioning
confidence: 99%
“…Reversal with naltrexone or diprenorphine results in rapid recovery (Bush 2003, Citino and Bush 2007). The use of a ketamine and medetomidine combination for immobilisation was also reported (Bush and others 2001, Flach and others 2002). …”
Section: Case Presentationmentioning
confidence: 95%
“…8,39 The latter approach has been popular over the past decade because of the avoidance of an opioid component and relatively smooth inductions; however, it may result in hypertension and tachypnea, and re-sedation from medetomidine as the reversal agent wears off is a real concern. 8,39 The latter approach has been popular over the past decade because of the avoidance of an opioid component and relatively smooth inductions; however, it may result in hypertension and tachypnea, and re-sedation from medetomidine as the reversal agent wears off is a real concern.…”
Section: Immobilization and Anesthesiamentioning
confidence: 99%